2020
DOI: 10.21203/rs.2.21580/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Utilization pattern of kangaroo mother care after introduction in eight selected neonatal intensive care units in China

Abstract: Background: Kangaroo mother care (KMC) is an evidence-based and cost-effective intervention that could prevent severe complications for preterm babies, however it has not been widely adopted in China. In this study, we aim to investigate the feasibility and parental experience of adopting KMC in a Chinese context by studying the implementation of a KMC program in eight self-selected neonatal intensive care units (NICUs).Methods: A cross-sectional study of 135 preterm infants discharged from eight NICUs in Apri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…16 KMC seems to be well accepted and bears no adverse effects. 12,17 In this study, we found that duration of hospitalization was significantly less among neonates of KMC group versus controls…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…16 KMC seems to be well accepted and bears no adverse effects. 12,17 In this study, we found that duration of hospitalization was significantly less among neonates of KMC group versus controls…”
Section: Discussionsupporting
confidence: 47%
“…A recent study from China consisting of 8 NICU settings revealed that KMC was well embraced by the parents and resulted in anxiety reduction along with improved communication among parents and medical staff. 12 A local study in NICU settings revealed that intermittent KMC was effective in improving weight-gain among neonates in addition to conventional care (average weight gain in grams per kg per day as 10.22±1.65 grams in KMC groups versus 7.87±1.71 grams among controls) but one of the limitation of that study was that body weight among neonates of KMC group was significantly higher at the start of the study period in comparison to controls (2.56±0.8 kg in KMC group versus 2.13±0.70 kg in controls). 13 A randomized controlled trial from India by Suman RP et al evaluating KMC care among LBW babies revealed average weight gain of 23.99 grams among KMC group in comparison to 15.58 gram among controls.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our study showed positive association between knowledge of KMC practice and the type of family the motheris living in.Those mothers from extended family were two times likely to have adequate knowledge on KMC practice compared to the mothers from nuclear family. Studies conducted elsewhere documented the importance of family support on KMC practice to the mother after home discharge [40,41], although did not indicate the knowledge differences between type of families. In the extended family, the inhabitants are beyond father, mother and children; where possibly, they might have learned from one another, should one among them ever experienced similar problem in the family, compared to nuclear family whereonlyhusband and wife live.…”
Section: Discussionmentioning
confidence: 88%